LOW-TEMPERATURE BEHAVIOUR OF HAEMATITE: SUSCEPTIBILITY AND MAGNETIZATION INCREASE ON CYCLING THROUGH THE MORIN TRANSITION - De Boer C.B.; Mullender T.A.T.; Dekkers M.J. (My University, 2001)
It has been realized previously (e.g. Borradaile 1994) that cycling through the Morin transition (Tm, occurring in ideal a-Fe2O3 at -10 °C) may have implications for the NRM of some haematite-bearing rocks. We investigate the behaviour of the low-field susceptibility (xlf), several magnetizations (in fields of 5, 25, 100 and 1600 mT) and SIRM on cycling through Tm of several well-characterized haematite types of varying crystallinity and particle shape. Before low-temperature treatment, xlf of the haematites varied between ~40 and ~235*10^(-8) m^3 kg^(-1). Below Tm, where only haematite's defect moment resides, xlf was much more uniform at ~19 to ~28*10^(-8) m^3 kg^(-1). After return to room temperature, increases in xlf of up to ~50 per cent were observed (when cycling in the Earth's magnetic field as well as in a field-free space), inferred to be a function of the domain state of the haematite. This was shown for one of the haematites (LH2 which occurs as small platelets and is particularly well crystalline) where a relation y=(8.60±1.01) ln(x)-2.98 was obtained, where x is the grain size (mm) and y is the percentage susceptibility increase.We suggest that transdomain changes induce the change in xlf. The nucleation of (additional) domain walls in metastable single-domain (SD) to pseudo-single-domain (PSD) grains is made possible by the low anisotropy at the Morin transition. In view of this mechanism, small stable SD haematite particles would not be affected and the grain size corresponding to y=0 (~1.5 mm for LH2) would represent the real SD threshold size. Thermal cycling to over the Curie temperature (680 °C) is needed to return to the original domain state before the LT treatment, as expressed by a return to the original xlf values. Measuring xlf between alternating field (AF) demagnetization steps shows that AF demagnetization gradually removes the xlf increase, which appears to be soft; 30 mT is sufficient to erase 90 per cent. Thermal cycling in a 5 mT field between temperatures above Tm showed that irreversible changes in domain structure are noticeable before the isotropic point is passed. After cycling, magnetization is added to PSD and multidomain (MD) grains that intriguingly appears to be remanence, probably induced by the broadening and subsequent irreversible displacement of loosely pinned domain walls. Complete cycling through the isotropic point considerably enhances the new remanence component in metastable SD to MD particles by an increase in the number of domains. If this behaviour can be extrapolated to the intensity of the Earth s magnetic field, this would imply that large metastable SD to MD specularite crystals with a well-developed Morin transition are susceptible to acquiring geologically irrelevant remanence components when subjected to low ambient temperatures. Fine-grained haematite pigment, on the other hand, would not be affected. Thermal demagnetization alone would not be able to separate these two remanences as the new domain structure persists up to close to the Curie temperature. Our findings indicate that a cleaning procedure consisting of an initial AF step followed by stepwise thermal demagnetization is preferable in order to isolate the original remanence component properly in haematite-bearing rocks.